Effect of Additional Hip Strengthening on Anterior Knee Pain, Strength, and Health Status in Patients with Total Knee Replacement: A Pilot Randomized Clinical Trial (International Journal of Physiotherapy, 2021)
Background: Total knee replacement (TKR) is a standard surgical option for advanced-stage knee osteoarthritis. The primary indication of TKR is incapacitating knee pain. 75% to 89% of patients undergoing TKR reports a satisfactory reduction in pain. However, some patients develop anterior knee pain post-TKR. Therefore, different treatment strategies are used for the management of pain post TKR. In the present study, we aimed to evaluate the additional effects of hip strengthening on pain, muscle strength, and health status in TKR patients.Methods: We randomized patients into two groups: knee group and knee hip group. The knee group (n=6) did knee flexors and extensors strengthening. The knee hip group (n=6) performed knee strengthening with additional hip abductors, lateral rotators, and extensors strengthening exercises. Both groups received four-session/week for six weeks. The pain was measured on NPRS, muscle strength on a hand-held dynamometer, and health status using the WOMAC scale. The data was collected at the baseline and post intervention (six weeks).Results: The knee hip group shows more marked improvements in pain than the knee group, t value =3.3 (p=0.012). The data did not suggest any difference in knee muscle strength between the groups. Hip muscle strength showed a significant difference. Health status significantly improved in the knee hip group compared to the knee group, t value = 4.68 (p=0.005).Conclusion: We can conclude that a six-week hip muscle strengthening exercise program effectively improves pain, muscle strength, and health status than a conventional knee strengthening program.